Determination of Changes in Yield and Profitability of Improved Soybean Production in Guinea Nigeria: A Case Study of Borno and Kaduna States - Wakawa, R. C. (Current Topics in Agricultural Sciences Vol. 4, 2021)
The study analyzed the profitability of improved soybean technology due to changes in yield among farming households in Guinea Nigeria. It mainly assessed the soybean yield before and after adopting the adopting the improved soybean technology; evaluate the cost and returns associated with the changes among the producers and examine the constraints of using the improved soybean technology in the study area. Using a multistage sampling technique, primary data has been collected from 162 respondents in the (Tropical Legume II) TL II and non-TL II communities in the study area. The results of the double difference (DD) estimate revealed a significant difference in crop yields before and after the project. According to the results of the gross margin analysis, the mean gross income of the TL II participants was N36,770.5 higher than that of the non-TL II participants, indicating that improved crop production is profitable in the study area. According to descriptive statistics, the major constraints faced by respondents include pests and diseases, a lack of a market, and a low price for soybeans, among other things. In view of the above, it is recommended that the TL II project be replicated by the governments of Borno and Kaduna, as well as other interested parties. Farmers who do not have TL II should learn from the improved soybean farmers. Farmers should be properly linked to existing soybean markets, and the TL II project should create more to consume the surplus. The TL II project must train farmers on soybean management practises and how to control pests and diseases.